IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KABUPATEN MUSI BANYUASIN NO 11 TAHUN 2016 TENTANG KAWASAN TANPA ROKOK PADA DINAS KESEHATAN KABUPATEN MUSI BANYUASIN - Sisca Nopralia; Hermansyah Hermansyah; Isma Nirmala; Siti Waliah (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
The research was carried out at the Musi Banyuasin district health office which is located at Jalan Kol. Wahid Udin No. 230 Kelurahan Kayuara, Sekayu District, Postal Code 30711, Sekayu, South Sumatra. The research used a descriptive approach, namely solving problems investigated by describing, describing the condition of the subject / object of the study (a person, institution, community, etc.) based on the facts and then described descriptively. The formulation of the problem examined in the study was How to Implement Regional Regulation number 11 of 2016 regarding smoking-free areas at the Musi Banyuasin District Health Office. Data collection techniques used are interviews, observation and documentation. The implementation model used is the implementation model according to George C. Edward III which includes four elements, namely communication measured through indicators of clarity and consistency, resource elements measured through staff indicators, information, authority, and facilities, disposition elements measured by appointment. employees and incentives, as well as elements of bureaucratic structure as measured by indicators of standard operating procedures (SOPs) and fragmentation. The results of the research that have been concluded are the implementation of Regional Regulation number 11 of 2016 concerning smoking-free areas at the Musi Banyuasin District Health Office which analyzed with the four elements above that have been communicated actively and clearly, including both vertical (superior to subordinate) and horizontal (among staff) directly or indirectly, have the resources to support it. The resources in question include competent and capable human resources (HR) as well as budgetary resources (SDA) originating from APBD funds, the disposition (attitude and willingness) of implementers who are involved in implementing the regional regulations without smoking are those who work. based on their capabilities and expertise, according to standard operating procedures (SOPs) and fragmentation (coordination of tasks) internally and externally.